Recent French Developments - Musselin, Christine; Mignot-Gerard, Stephanie (International Higher Education, 2015)
French universities have long been known for their weak governance capacity. Research by Erhard Friedberg and Christine Musselin on this topic (Enquête d’universités, 1989) and their comparative work on French and German universities clearly confirmed this characteristic. They show that French university administrators tend to behave as primus inter pares rather than as active promotors of collective projects. In most cases, university bodies came to “␣ nondecisions,” not making any decisions at all, rubberstamping choices made by individual faculty members, leaving the final decision to the ministry, or simply implementing the criteria set by the Parisian central administration. Thus, individual autonomy was considerable while institutional autonomy was limited␣ ; moreover the latter was considered somewhat illegitimate. In the view of these two authors, the weak governance of French universities allowed the Ministry of Education to play an interventionist role that also maintained the weakness at the institutional level. Fifteen years later, the authors of this article have done a new study on French university governance, funded by the Agency for the Modernization of the Universities—created in 1997 as part of the French Association of University Presidents. Based on 250 in-depth interviews at four universities, the study shows that French universities experienced a number of important changes within the last decade and have strengthened their governance.